Comparative analysis of the integument transcriptomes of the black dilute mutant and the wild-type silkworm Bombyx mori - Wu, Songyuan; Tong, Xiaoling; Peng, Chenxing; Xiong, Gao; Lu, Kunpeng; hu, Hai; Tan, Duan; Li, Chunlin; Han, Minjin; Lu, Cheng; Dai, Fangyin (Scientific reports, 2016)
The insect cuticle is a critical protective shell that is composed predominantly of chitin and various cuticular proteins and pigments. Indeed, insects often change their surface pigment patterns in response to selective pressures, such as threats from predators, sexual selection and environmental changes. However, the molecular mechanisms underlying the construction of the epidermis and its pigmentation patterns are not fully understood. Among Lepidoptera, the silkworm is a favorable model for color pattern research. The black dilute ( bd ) mutant of silkworm is the result of a spontaneous mutation; the larval body color is notably melanized. We performed integument transcriptome sequencing of the wild-type strain Dazao and the mutant strains +/ bd and bd / bd . In these experiments, during an early stage of the fourth molt, a stage at which approximately 51% of genes were expressed genome wide (RPKM ≥1) in each strain. A total of 254 novel transcripts were characterized using Cuffcompare and BLAST analyses. Comparison of the transcriptome data revealed 28 differentially expressed genes (DEGs) that may contribute to bd larval melanism, including 15 cuticular protein genes that were remarkably highly expressed in the bd / bd mutant. We suggest that these significantly up-regulated cuticular proteins may promote melanism in silkworm larvae.